ASSESSMENT OF THE DIVERSITY OF BIRD SPECIES IN CAT BA NATIONAL PARK, HAI PHONG CITY - Minh Quang, Nguyen; Thanh Hai, Dong; Van Thap, Hoang (Journal of Forestry Science and Technology, 2016)
Cat Ba National Park (NP) is considered as a potential area in terms of biodiversity conservation due to its diversified species and habitat. However, little information on the diversity of fauna in the park is available for conservation and management. The aim of this study is to investigate the species composition of bird, their distribution as well as threats to the species and its habitat. Line transect and mist net were used to collect data in the field. The results of the study reveal that there are 209 bird species belonging to 51 families, 17 orders in the park. The observed species distributed mostly in natural forests, followed by artificial forests and mixed of natural and artificial forests; in the shrub and grassland was the habitat with least species observed compared to the 3 mentioned habitats. We also identified 17 bird species as a high value for conservation Hunting, trapping, wood and Non-timber forest product (NTFPs) exploiting, forestfire, grazing catlle, tourism are the main threats to the bird species and their habitats.